2003
DOI: 10.1007/s11746-003-0789-7
|View full text |Cite
|
Sign up to set email alerts
|

Applications of immobilized Thermomyces lanuginosa lipase in interesterification

Abstract: The aim of this work was to investigate the catalytic functions of a new immobilized Thermomyces lanuginosa lipase in interesterification and to optimize the conditions of interesterification for the production of human milk fat substitutes (HMFS) containing n-3 PUFA by response surface methodology (RSM). Thermomyces lanuginosa lipase had an activity similar to that of immobilized Rhizomucor miehei lipase (Lipozyme RM IM) in the glycerolysis of sunflower oil, but the former had higher activity at a low reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 20 publications
2
40
0
2
Order By: Relevance
“…The choice of the proper substrate molar ratio is also related to the downstream processing expenses and associated diiculties of separating FFAs or acyl donors by evaporation and/or distillation. Previous studies have shown that high substrate molar ratio would require a shorter reaction time, move the reaction equilibrium to the product formation, and improve the acyl incorporation [114,115]. Yang et al [114] reported the positive efect of substrate molar ratio on the interesteriication reaction between EPA and DHA ethyl esters and tripalmitin.…”
Section: Substrate Composition and Concentration (Molar Ratio)mentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the proper substrate molar ratio is also related to the downstream processing expenses and associated diiculties of separating FFAs or acyl donors by evaporation and/or distillation. Previous studies have shown that high substrate molar ratio would require a shorter reaction time, move the reaction equilibrium to the product formation, and improve the acyl incorporation [114,115]. Yang et al [114] reported the positive efect of substrate molar ratio on the interesteriication reaction between EPA and DHA ethyl esters and tripalmitin.…”
Section: Substrate Composition and Concentration (Molar Ratio)mentioning
confidence: 99%
“…Previous studies have shown that high substrate molar ratio would require a shorter reaction time, move the reaction equilibrium to the product formation, and improve the acyl incorporation [114,115]. Yang et al [114] reported the positive efect of substrate molar ratio on the interesteriication reaction between EPA and DHA ethyl esters and tripalmitin. They indicated that the optimization results suggested a molar ratio of 6 along with an enzyme load of 20% (Lipozyme TL-IM) and a 17.9 h reaction time would provide the highest incorporation.…”
Section: Substrate Composition and Concentration (Molar Ratio)mentioning
confidence: 99%
“…13,38,49,73,[78][79][80][81][82][83] Pesquisadores patentearam diferentes métodos de produção de lipídios estruturados e utilização em fórmulas infantis na Europa 84 e na Austrália. 78 Diferentes tipos de óleos e gorduras são utilizados como substratos para a produção de lipídios estruturados sucedâneos da gordura do leite humano, como o tripalmitoilglicerol, gordura suína (banha), gordura do leite bovino, óleo de soja, óleo de canola, óleo de borage e óleo de girassol.…”
Section: Lipídios Estruturados -Sucedâneos Dos Lipídios Do Leite Humanounclassified
“…Yang et al 83 utilizaram as enzimas Lipozyme IM ® TL de Thermomyces lanuginosa para interesterificar o tripalmitoilglicerol com ácido caprílico e óleo de girassol, visando produzir lipídio estruturado semelhante ao lipídio do leite humano. As melhores incorporações de ácido palmítico (42%) foram obtidas nas seguintes condições: 20% de enzima por 20 h de reação a 40 ºC.…”
Section: Figura 1 Estrutura Do Principal Triacilglicerol Do Betapolunclassified
“…Among them, enzyme immobilization is a widely employed method to impart the desirable features of enzymes 14,15 . Immobilized lipase provides important advantages to the process, such as the ease in catalyst recycling, continuous operation, and product purification.…”
Section: Introductionmentioning
confidence: 99%